Correlation between refractive errors and corneal thickness in a sample of iraqi population witha wide range of ametropia - Abbas, Muthanna Abdulkhudhur; Alhammami, Dr.Hussein (Karbala Journal of Medicine, 2019)
Purpose: To determine the Correlation between Refractive Error and Central Corneal Thickness in A NAJAF Population with a Wide Range of Ametropia . Setting AL HAKEEM General Hospital, ANAJAF, Iraq. 2014-2015 Patients and methods In a cross sectional observational study, Involved 399 eyes of 200 Patients For whom the central corneal thickness(CCT)was measured with Ultrasonic pachymetry (TOMEY PACHYMETER SP-3000). The refractive error, including sphere, cylinder, and spherical equivalent (SE), were measured with Topcon (KR.8900) autorefractometer And Manual refraction. Examination of anterior segment using slit lamp and fundoscopy using volk + 90 D, were done to exclude any underlying pathology Results The mean age of the study subjects was 30.71(range, 17 to 61 )years. The mean spherical equivalent (SE) of the right eye was -3,2475 Diopter (range,-11.25 to 5.75 Diopters) while SE of the left eye was-3,2035 Diopter (range,-14.5 to 8.5 Diopters).The mean central corneal thickness(CCT) of the right eye 533,1600 Micron (range,407.00 to 635.00 Micron) while CCT of the left eye was 532,7638 Micron (range,394.00 to 630.00 Micron).No significant correlation were found between spherical equivalent (SE) and central corneal thickness (CCT) of right and left eye among the studied group. Conclusion No significant Relation found between Refractive errors and central corneal thickness (CCT).